2005
DOI: 10.1080/00016480510036457
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the lymphatic drainage system of the nose and paranasal sinuses and its role in detection of sentinel metastatic nodes

Abstract: Our control group comprised 30 patients (20 females; age range 19-50 years) suffering from chronic otitis media who had an anatomically normal nose and a cNO neck on palpation. The pathological group comprised 6 patients (2 females; age range 40-85 years) suffering from sinonasal tumors: 3 SCC, 1 recurrent melanoma, 1 ameloblastoma and 1 inverted papilloma. All had a clinically staged cNO neck on palpation and CT. In the control group, lymphoscintigraphy was carried out by means of unilateral injection of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…Dynamic MR imaging can differentiate accurately recurrent IP from postoperative changes [307]. Lymph nodes can also be assessed with MRI with similar size and peripheral characteristics as for CT. Involved nodes are heterogeneous on T2 weighting and enhance peripherally on contrast scans using fat suppression [300, 308]. Further advantages of MRI are that images can be obtained in multiple planes, there is no exposure to ionizing radiation, and there is no artefact in the presence of dental fillings.…”
Section: Work-up Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic MR imaging can differentiate accurately recurrent IP from postoperative changes [307]. Lymph nodes can also be assessed with MRI with similar size and peripheral characteristics as for CT. Involved nodes are heterogeneous on T2 weighting and enhance peripherally on contrast scans using fat suppression [300, 308]. Further advantages of MRI are that images can be obtained in multiple planes, there is no exposure to ionizing radiation, and there is no artefact in the presence of dental fillings.…”
Section: Work-up Investigationmentioning
confidence: 99%
“…The retropharyngeal nodes comprise the first echelon lymphatic drainage for sinus malignancies. Cervical lymph node are involved with T2 rather than T3 or T4 tumors of squamous cell histology [241, 308]. Other regional nodes that may be involved with lymphatic spread are the periparotid and level 1b nodes [257].…”
Section: Stagingmentioning
confidence: 99%
“…10 Fernandez et al performed a clinical evaluation of drainage patterns after injection of radiocolloid into the head of the inferior turbinate and demonstrated that the majority of the drainage was to level 1 and level 2 cervical lymph nodes and less commonly to the retropharynx. 5 In cases of sinonasal melanoma, though in general more anterior lesions will drain into the submandibular and jugulodigastric nodes and the more posterior lesions will drain into the retropharyngeal area, these neoplasms are often large and span multiple subsites, putting several drainage pathways at risk for regional metastasis. Though the rate of the regional spread at presentation is reported to be 5 to 20%, approximately 20 to 40% of patients will have a regional recurrence that complicates their disease course.…”
Section: Discussionmentioning
confidence: 99%
“…4 Some authors have questioned whether elective ipsilateral nodal dissection is warranted given the high rate of cervical metastasis at some point in the disease course; however, the lymph node basins of the sinonasal cavity are variable and posterior lesions would be expected to travel to the retropharyngeal nodes, making decisions on the extent of lymph node dissection difficult. 3,5,6 Sentinel node biopsy offers an opportunity to perform guided lymph node biopsy for at-risk lymph node basins with minimal morbidity. 7,8 We hypothesize that sentinel node biopsy would offer a minimally invasive approach to staging and treatment of the cervical nodal basin in sinonasal melanoma and report our initial experience of two patients with positive sentinel node biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…As far as histogenetic considerations about sinonasal AM origin is concerned, some studies have indicated a close relation of the embryological derivation of the sinonasal tract and odontogenic apparatus [1, 4, 5, 1316, 22]. The sinonasal tract and oral cavity communicate, in fact, until closure of the palatine shelves.…”
Section: Discussionmentioning
confidence: 99%